Reason and emotion in working-class religion, 1794–1824 - Mews, Stuart (Studies in church history, 1972)
In the last decade considerable attention has been paid to Methodism, revivalism, and the development of working-class consciousness in early nineteenth-century England. The purpose of this paper is to add a few footnotes and caveats to some of the assertions which have been made about these topics. The assertions on which I wish to comment can be divided into two groups. The first includes the view widely accepted by sociologists and social historians that in so far as working-class people resort to religion in periods of rapid social change, the religious style which they adopt tends to be of an highly emotional type. Hence the numerical success of Methodism in the lower if not the lowest regions of the social scale is attributed to the prominence which it gave the experiential dimension of religious commitment. On the other hand a religious system like Unitarianism which was theologically highly rational and stressed the intellectualist dimension is dismissed, almost on a priori grounds from having any popular appeal. K. S. Inglis after claiming that before 1850 the Unitarians were ‘uninterested in evangelizing the masses’, quotes G. M. Trevelyan to the effect that theirs was ‘a faith likely to be taken up by the mill-owner but not by his workmen’. According to E. P. Thompson ‘it seemed too cold, too distant, too polite and too much associated with the comfortable values of a prospering class to appeal to the city or village poor’. The first area in which I wish to submit new evidence is concerned therefore with the general relationship between working-class religion and reason and emotion.